2021
DOI: 10.1093/europace/euab176
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Sudden Unexpected Death in the Young (SUDY) in Europe: results of the European Heart Rhythm Association Survey

Abstract: The aims of this centre-based survey, promoted and disseminated by the European Heart Rhythm Association (EHRA) was to investigate the current practice for the investigation of Sudden Unexplained Death in the Young (SUDY) amongst European countries. An online questionnaire composed of 21 questions was submitted to the EHRA Research Network, European Cardiac Arrhythmia Genetics (ECGen) Focus Group members, and European Reference Network GUARD-Heart healthcare partners. There were 81 respondents from 24 European… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Therefore, the identification of a structurally normal heart in case of arrhythmic SCD is of equal importance as it does not exclude the presence of a genetically determined and potentially hereditary cardiac disease and a further evaluation with a multidisciplinary team approach is needed. Clear-cut criteria to define a normal heart are crucial [ 9 , 16 , 27 30 ]. Obviously, a detailed drug history is important and use of cocaine, steroids and methamphetamine sought as these can cause both hypertrophy and dilatation of the heart.…”
Section: The Pathologist Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the identification of a structurally normal heart in case of arrhythmic SCD is of equal importance as it does not exclude the presence of a genetically determined and potentially hereditary cardiac disease and a further evaluation with a multidisciplinary team approach is needed. Clear-cut criteria to define a normal heart are crucial [ 9 , 16 , 27 30 ]. Obviously, a detailed drug history is important and use of cocaine, steroids and methamphetamine sought as these can cause both hypertrophy and dilatation of the heart.…”
Section: The Pathologist Perspectivementioning
confidence: 99%
“…However, adherence to guidelines/recommendations is still suboptimal in many European countries. In up to 40% of cases, autopsies are not performed in subjects less than 50 years who may have died from cardiac disease and only 50% of pathologists declared to follow a standard protocol for autopsy examination, apparently due to lack of expertise and/or training [ 27 , 75 ].…”
Section: The Multidisciplinary Team Approachmentioning
confidence: 99%
“…Finally, despite the fact that molecular autopsy is widely recommended, it is not included in forensic protocols in most countries. The most recent survey conducted by the European Heart Rhythm Association for the Investigation on Sudden Unexpected Death in the Young (SUDY) in Europe reported that only 37% of SUD cases with a suspected arrhythmic cause undergo postmortem genetic testing, revealing a high heterogeneity in adherence to current recommendations for SUDY investigation (92,112). There are several reasons to avoid this implementation, such as economic considerations or legal restrictions involved with the sample collection, the storage time and the number of genes analyzed, as well as the ethical implications of genetic results obtained after a molecular autopsy (113).…”
Section: Recommendations/guidelinesmentioning
confidence: 99%
“…Despite its diagnostic yield and the guideline recommendations for molecular autopsy, there is substantial heterogeneity in adherence to guidelines as was highlighted in a recent survey initiated by the European Cardiac Arrhythmia Genetics (ECGen) Focus Group of the European Heart Rhythm Association (EHRA). The survey investigated the use of postmortem genetic studies, among other practices, across Europe and found that genetic material is extracted in less than half of SUDY cases and molecular autopsy is performed in only 37% of SADS cases [27 ▪ ].…”
Section: Sudden Death In the Youngmentioning
confidence: 99%